Longitudinal visual functional recovery in compressive optic neuropathy in patients with primary pituitary microadenoma after endoscopic transnasal surgery (Ukrainian Journal of Ophthalmology, 2025)
Background: Neoplasms of the chiasmal and optic nerve region can result in compressive optic neuropathy with reduced visual acuity (VA), visual field defects and primary descending optic atrophy. Anterior visual pathway compression by the neoplasm is an absolute indication for surgical intervention.Purpose: To review the phases of visual functional recovery in compressive optic neuropathy in patients with primary pituitary microadenoma after endoscopic transnasal surgery.Material and Methods: We retrospectively reviewed the records of 225 patients who were treated for pituitary adenoma at the Romodanov Neurosurgery Institute from 2017 through 2019. All patients (450 eyes) had optic nerve/chiasm complex (ONCC) compression, reduced VA and/or visual field defects preoperatively and underwent surgical decompression of the ONCC. The time points for eye examination were day 1 or 2 after hospitalization (time point 0), and day 5, 6 or 7 (early postoperative examination; time point 1), month 1 (time point 2), month 3 (time point 3), month 6 (time point 4), and month 12 (time point 5) after surgery.Results: In the majority of patients, decompression of the ONCC resulted in an improvement in or recovery of vision. There was a significant difference (p < 0.05) in VA and mean defect (MD) between time point 1 (VA: 0.74 ± 0.02; MD: 7.85 ± 0.29 dB) and time point 3 (VA: 0.8 ± 0.01; MD: 6.37 ± 0.28 dB). Moreover, there was a significant difference in MD between time point 1 (7.85 ± 0.29 dB) and time point 2 (6.91 ± 0.28 dB), and between time point 2 and time point 4 (6.08 ± 0.28 dB).Conclusion: After surgical decompression of the ONCC, we observed the two phases of visual functional recovery: fast (as long as several days) and delayed (until 6 months). There was practically no further improvement in visual functions after month 6.
Keywords: skull-base tumors; pituitary asenoma; chiasmal syndrome; compressive optic atrophy; phases of visual functional recovery; endoscopic transnasal surgery